Therapeutic Hypothermia after Cardiac Arrest: Experience at an Academically Affiliated Community-Based Veterans Affairs Medical Center - Maulik P. Shah; Leslie Zimmerman; Jean Bullard; Midori A. Yenari (Stroke Research and Treatment)
At laboratory and clinical levels, therapeutic hypothermia has been shown to improve neurologic outcomes and mortality following cardiac arrest. We reviewed each cardiac arrest in our community-based Veterans Affairs Medical Center over a three-year period. The majority of cases were in-hospital arrests associated with initial pulseless electrical activity or asystole. Of a total of 100 patients suffering 118 cardiac arrests, 29 arrests involved comatose survivors, with eight patients completing therapeutic cooling. Cerebral performance category scores at discharge and six months were significantly better in the cooled cohort versus the noncooled cohort, and, in every case except for one, cooling was offered for appropriate reasons. Mean time to initiation of cooling protocol was 3.7 hours and mean time to goal temperature of 33∘C was 8.8 hours, and few complications clearly related to cooling were noted in our case series. While in-patient hospital mortality of cardiac arrest was high at 65% mortality during hospital admission, therapeutic hypothermia was safe and feasible at our center. Our cooling times and incidence of favorable outcomes are comparable to previously published reports. This study demonstrates the feasibility of implementing, a cooling protocol a community setting, and the role of neurologists in ensuring effective hospital-wide implementation.